The 3PAs: An Update on the Association of Pheochromocytomas, Paragangliomas, and Pituitary Tumors - Xekouki, Paraskevi; Brennand, Ana; Whitelaw, Ben; Pacak, Karel; Stratakis, Constantine A. (Hormone and Metabolic Research, 2018)
Pituitary adenomas (PA) and pheochromocytomas/paragangliomas (PHEO/PGL) are rare tumors. Although they may co-exist by coincidence, there is mounting evidence that genes predisposing in PHEO/PGL development, may play a role in pituitary tumorigenesis. In 2012, we described a GH-secreting PA caused by an SDHD mutation in a patient with familial PGLs and found loss of heterozygosity at the SDHD locus in the pituitary tumor, along with increased hypoxia-inducible factor 1α (HIF-1α) levels. Additional patients with PAs and SDHx defects have since been reported. Overall, prevalence of SDHx mutations in PA is very rare (0.3–1.8% in unselected cases) but we and others have identified several cases of PAs with PHEOs/PGLs, like our original report, a condition which we termed the 3 P association (3PAs). Interestingly, when 3PAs is found in the sporadic setting, no SDHx defects were identified, whereas in familial PGLs, SDHx mutations were identified in 62.5–75% of the reported cases. Hence, pituitary surveillance is recommended among patients with SDHx defects. It is possible that the SDHx germline mutation-negative 3PAs cases may be due to another gene, epigenetic changes, mutations in modifier genes, mosaicism, somatic mutations, pituitary hyperplasia due to ectopic hypothalamic hormone secretion or a coincidence. PA in 3PAs are mainly macroadenomas, more aggressive, more resistant to somatostatin analogues, and often require surgery. Using the Sdhb+/− mouse model, we showed that hyperplasia may be the first abnormality in tumorigenesis as initial response to pseudohypoxia. We also propose surveillance and follow-up approach of patients presenting with this association.
Keywords: pituitary adenoma; pheochromocytoma; paraganglioma; succinate dehydrogenase